COMPUTATIONAL ANALYSIS OF MANGROVE DOMESTICATION: IMPACT ON COASTAL FLORA AND FAUNA IN MUMBAI - Nidhi Jain1, Mona Kejariwal2*, Lalana Khot3, Yogesh kadam4,Megha Patil5, Deenanath Jhade6, Praveen Sharma7 (Chelonian Research Foundation, 2024)
Mangrove ecosystems, renowned for their high productivity, exhibit remarkable sensitivity and fragility. These forests undergo constant seasonal, short-term, and long-term changes, driven by their dynamic nature and various natural and biotic influences. Playing a pivotal role, mangrove forests not only support coastal marine organisms but also act as a shield against erosion, serving as crucial breeding, feeding, and nursery grounds for estuarine and marine life. Moreover, they contribute significantly to capture and culture fisheries. Thus, regular monitoring of mangrove habitats is imperative for comprehensive coastal marine ecological studies and effective coastal management.The sustainability of the mangrove ecosystem holds paramount importance for Mumbai, one of the world's premier mega-cities with a population exceeding 13 million, facing significant demographic pressures. Anthropogenic activities, often associated with development projects, have frequently led to the depletion of coastal resources, destruction of critical habitats, disruption of ecosystem processes, and loss of biodiversity. Given these challenges, accurate mapping of this invaluable land resource becomes essential, particularly considering the livelihoods of the 50,000 fishermen in Mumbai. This review focuses on the computational analysis of Mangrove Domestication and its Impact on Coastal Flora and Fauna. Keywords: Mangrove Domestication; Flora and Fauna; Mumbai; Computational analysis; Coastal zone.